Wisdom from the late Bronze Age - Cohen, Yoram; George, Andrew (Writings from the ancient world, 2013)
Part 1.Introduction. A general overview of the compositions and their sources --Definitions and approaches --The historical and social contexts --The archaeological and archival contexts --The curricular context: the place and role of wisdom literature within the Scribal-school curriculum --Part 2.Late Bronze Age Wisdom compositions. Šimâ milka, or The instructions of Šūpê-amēli --The ballad of early rulers --Enlil and Namzitarra --The righteous sufferer or A hymn to Marduk from Ugarit --The date palm and the Tamarisk --Proverb collections from Ḫattuša --An Akkadian-Hurrian bilingual proverb extract --Proverbs and proverbial sayings in letters: the Mari letters and late Bronze Age correspondence.